2D Freestanding Janus Gold Nanocrystal Superlattices. Issue 28 (9th May 2019) - Shi, Qianqian; Gómez, Daniel E.; Dong, Dashen; Sikdar, Debabrata; Fu, Runfang; Liu, Yiyi; Zhao, Yumeng; Smilgies, Detlef‐M.; Cheng, Wenlong
Abstract: 2D freestanding nanocrystal superlattices represent a new class of advanced metamaterials in that they can integrate mechanical flexibility with novel optical, electrical, plasmonic, and magnetic properties into one multifunctional system. The freestanding 2D superlattices reported to date are typically constructed from symmetrical constituent building blocks, which have identical structural and functional properties on both sides. Here, a general ligand symmetry‐breaking strategy is reported to grow 2D Janus gold nanocrystal superlattice sheets with nanocube morphology on one side yet with nanostar on the opposite side. Such asymmetric metallic structures lead to distinct wetting and optical properties as well as surface‐enhanced Raman scattering (SERS) effects. In particular, the SERS enhancement of the nanocube side is about 20‐fold of that of the nanostar side, likely due to the combined "hot spot + lightening‐rod" effects. This is nearly 700‐fold of SERS enhancement as compared with the symmetric nanocube superlattices without Janus structures. Abstract : A general ligand symmetry‐breaking strategy is introduced to design and fabricate 2D Janus gold nanocrystal superlattice sheets with a nanocube on one side yet with a nanostar on the opposite side. Such asymmetric structures display distinct morphology‐dependent surface wettabilities, optical properties, and surface‐enhanced Raman scattering effects between the two sides, providing a novel way to design and tune the material properties of 2D superlattices.